2021
DOI: 10.1039/d1ma00448d
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable electrochemical and ion-transport characteristics of magnesium-fluorinated alkoxyaluminate–diglyme electrolytes for magnesium batteries

Abstract: Magnesium batteries (MBs) are fascinating options for large-scale energy-storage devices because the properties of magnesium metal anodes are more advantageous than those of their lithium or sodium counterparts. Moreover, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(79 citation statements)
references
References 68 publications
4
75
0
Order By: Relevance
“…the improved ionic conductivity. [38] However, we believe this to be unlikely, as previous reports in lithium-ion electrolytes have shown that anion trapping results in a decrease of the overall ionic conductivity of the electrolyte. [39] Finally, the solvation of Ca(BF 4 ) 2 in organic carbonate solvents, both single and equimolar mixtures, was found to be highly solvent-dependent.…”
Section: Electrolytes With Borohydrides and Other Boron-containing An...mentioning
confidence: 79%
See 1 more Smart Citation
“…the improved ionic conductivity. [38] However, we believe this to be unlikely, as previous reports in lithium-ion electrolytes have shown that anion trapping results in a decrease of the overall ionic conductivity of the electrolyte. [39] Finally, the solvation of Ca(BF 4 ) 2 in organic carbonate solvents, both single and equimolar mixtures, was found to be highly solvent-dependent.…”
Section: Electrolytes With Borohydrides and Other Boron-containing An...mentioning
confidence: 79%
“…The formation of anion–solvent complexes and hence the decrease of anion mobility and increase in t + , suggested by MD simulations, is presented as the origin for the improved ionic conductivity. [ 38 ] However, we believe this to be unlikely, as previous reports in lithium‐ion electrolytes have shown that anion trapping results in a decrease of the overall ionic conductivity of the electrolyte. [ 39 ]…”
Section: Mg2+ and Ca2+ Cation Solvationmentioning
confidence: 93%
“…The electrolyte was synthesized according to a previously reported procedure. [19,27] A current density of 1 mA cm À 2 for 30 min for each dissolution and deposition at 30 °C was adopted for both the symmetric and asymmetric assemblies. Galvanostatic discharge-charge cycling was also performed on the [pMg or AZ31 alloy j 0.3 mol dm À 3 Mg[B-(HFIP) 4 ] 2 /G2 j MgMn 2 O 4 or α-MnO 2 ] cells.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…These electrolytes exhibit excellent compatibility against an Mg metal anode. [16][17][18][19][20] Owing to the absence of strong corrosive components, their anodic stability is high enough to be compatible with transition metal oxides. 7,8 In this study, the discharge-charge performance of ZnMnO 3 at ambient temperature was investigated using one such representative electrolyte, i.e., Mg[B(HFIP) 4 ] 2 /G3.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…Important research on prototype MRBs was reported in 2000 where a certain Chevrel-phase compound (e.g., Mo 6 S 8 ), Mg metal, and the tetrahydrofuran solutions of Mg organohaloaluminate salt (e.g., Mg(AlCl 2 BuEt) 2 ) were used as a cathode, anode, and electrolyte, respectively. 2 Since this pioneering work, several efforts have been made to develop novel cathode, [3][4][5][6][7][8][9][10][11][12] anode, [13][14][15] and electrolyte materials [16][17][18][19][20] to realize practical MRBs. However, research into MRB materialization remains in a primitive stage because of several serious issues arising from the intrinsic chemical and electrochemical characteristics of Mg metal anodes and Mg 2+ (Mg ions).…”
Section: Introductionmentioning
confidence: 99%